Organisational Development and Institutional Strengthening (ODIS) of Planning and Programming Directorate of the Ministry of Agriculture and Natural Resources (PPD-MOANR) - , Dawit Hailegiorgis (Archives of Current Research International, 2017)
The study is primarily aimed to help improve PPD to enhance its functional linkages and working relationships with other MoANR units and regional bureaus of agriculture. The study conducted from February 2017 to March 2017 based in Velp, Netherlands. The report involved a desk study of official documents and other literature. Integrated Organization Model (IOM) has been utilised to describe the organisational development of PPD. Political, Economic, Sociocultural, Technological and Environmental (PESTE) has been utilised to describe and explain the institutional environment and canvas business model has been employed to analyse the PPD. The finding from analysis shows that PPD structure has 3 case teams and 26 professionals. Planning, monitoring, evaluation and reporting are integral parts of the management function, at various levels and across functional/ technical units. PPD plays a significant role in the preparation of the agricultural sector plan, in collaboration with the various MoANR (core and supporting directorates), centres and institutions. The primary inputs of PPD are its staff, budget, office equipment and support from its partners. The main output of PPD includes; prepared regular plans, program and project, bilateral and multilateral cooperation agreements and policy and socioeconomic studies. The internal strength includes; human resources and management body that is ready for change and presence of completed and ready Business Process and Reengineering/BPR while weaknesses are planning and programming do not follow strategical thinking and limited implementation capacity of staff. The external opportunities include; implementation of program budget and BPR while variation in the implementation of BPR identified as a threat. Recommendation drawn from the study findings demand raising PPD’s technical and professional profile through technical support and strategic partnerships alongside a long term human resource development activities and improving staff motivation.